Mesenchymal stem cells and exosomes improve cognitive function in the aging brain by promoting neurogenesis - Zhang, Xiaowen; Hou, Xuejia; Te, Liu; Zhongsheng, Zhou; Jiang, Jinlan; Wu, Xiaodong (Frontiers in Aging Neuroscience, 2022)
Biologically speaking, normal aging is a spontaneous and inevitable process of organisms over time. It is a complex natural phenomenon that manifests itself in the form of degenerative changes in structures and the decline of functions, with diminished adaptability and resistance. Brain aging is one of the most critical biological processes that affect the physiological balance between health and disease. Age-related brain dysfunction is a severe health problem that contributes to the current aging society, and so far, there is no good way to slow down aging. Mesenchymal stem cells (MSCs) have inflammation-inhibiting and proliferation-promoting functions. At the same time, their secreted exosomes inherit the regulatory and therapeutic procedures of MSCs with small diameters, allowing high-dose injections and improved therapeutic efficiency. This manuscript describes how MSCs and their derived exosomes promote brain neurogenesis and thereby delay aging by improving brain inflammation.